PEMBERIAN WARNA CAHAYA BERBEDA TERHADAP PERTUMBUHAN DAN KANDUNGAN SENYAWA ANTIOKSIDAN DALAM DAUN TANAMAN KRISAN (Chrysanthemum sp) - Agus Rizki Ansori; Denna Eriani Munandar; Fitria Riany Eris (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2019)
Chrysanthemum plants besides being used as ornamental plants and cut flowers can also be useful in the world of health, namely as herbal tea. The parts of the plants used are leaves, flowers or both at once. The addition of different light colors in chrysanthemum plants is expected to improve the quality of chrysanthemum tea by increasing antioxidant compounds in chrysanthemum leaves. This study aims to determine the effect of the addition of different light colors on the growth and content of antioxidant compounds in the leaves of these plants. This research using Complete Randomized Design (CRD) consisting of 4levels with 5 replications. The treatments given were 4 different colors namely white (W1), red (W2), yellow (W3), blue (W4). Observation data were analyzed using analysis of variance (ANOVA), if there was a significant difference, then Duncan's Multiple Distance Test was conducted at 95% confidence level. The addition of different light colors had a very significant effect on total fresh weight, leaf fresh weight, fresh weight of stover and antioxidant activity then significantly affected plant height, total dry weight, leaf dry weight and dry weight of stover. But the number of leaves shows an unreal effect. The results showed that the addition of blue and yellow light colors had the highest effect on the content of antioxidant compounds.